Arabidopsis F‐BOX STRESS INDUCED 4 is required to repress excessive divisions in stomatal development. Issue 1 (21st January 2022) - Li, Yi; Xue, Shan; He, Qixiumei; Wang, Junxue; Zhu, Lingling; Zou, Junjie; Zhang, Jie; Zuo, Chaoran; Fan, Zhibin; Yue, Junling; Zhang, Chunxia; Yang, Kezhen; et al.
Abstract: During the terminal stage of stomatal development, the R2R3‐MYB transcription factors FOUR LIPS (FLP/MYB124) and MYB88 limit guard mother cell division by repressing the transcript levels of multiple cell‐cycle genes. In Arabidopsis thaliana possessing the weak allele flp‐1, an extra guard mother cell division results in two stomata having direct contact. Here, we identified an ethylmethane sulfonate‐mutagenized mutant, flp‐1 xs01c, which exhibited more severe defects than flp‐1 alone, producing giant tumor‐like cell clusters. XS01C, encoding F‐BOX STRESS‐INDUCED 4 (FBS4), is preferentially expressed in epidermal stomatal precursor cells. Overexpressing FBS4 rescued the defective stomatal phenotypes of flp‐1 xs01c and flp‐1 mutants. The deletion or substitution of a conserved residue (Proline166) within the F‐box domain of FBS4 abolished or reduced, respectively, its interaction with Arabidopsis Skp1‐Like1 (ASK1), the core subunit of the Skp1/Cullin/F‐box E3 ubiquitin ligase complex. Furthermore, the FBS4 protein physically interacted with CYCA2;3 and induced its degradation through the ubiquitin‐26S proteasome pathway. Thus, in addition to the known transcriptional pathway, the terminal symmetric division in stomatal development is ensured at the post‐translational level, such as through the ubiquitination of target proteins recognized by the stomatal lineage F‐box protein FBS4. Abstract : Arabidopsis F‐BOX STRESS‐INDUCED 4 (FBS4) is preferentially expressed in stomatal precursor cells in leaf epidermis. FBS4 interacts with CYCLIN A2;3 and induces its degradation via the ubiquitin‐26S proteasome pathway, preventing cell over‐proliferation during the terminal division of stomatal development.